Selection response in fish and shellfish: a review - Trygve Gjedrem; Morten Rye (Reviews in Aquaculture, 2018)
The aquaculture sector is significantly behind plant and farm animal production in applying selective breeding, in spite of the fact that it has been suggested that the world aquaculture production could be doubled in 13 years if breeding programmes were supplying stocks for the farmed species. It is estimated that as late as in 2010, only 8.2% of the world's total aquaculture production was based on material developed in selective breeding programmes. Reported estimates of genetic gain per generation for a key trait like growth rate average 13%, implying that the animal's potential for growth can be doubled in a time span of only six generations of selection, as demonstrated for major farmed species like Atlantic salmon and Nile tilapia. Likewise are reported genetic gains for improved disease resistance generally very high. This study offers an updated review of published estimates on genetic gains for a range of traits in aquaculture species. Results are highly encouraging and demonstrate a substantial potential for genetic improvement in aquatic productions, in particular for traits such as growth rate and resistance to diseases.